PEMBANGUNAN KARAKTER KEARIFAN LEGENDA SARIP TAMBAK OSO BAGI GENERASI - Joko Susilo; Niko Fediyanto (Jurnal Abadimas Adi Buana, 2018)
Storytelling is a way to transfer knowledge from generation to generation, but sometimes the process is interrupted due to some disturbing factors from outside the cultural society. This program is designed to generate the activity of storytelling with "Sarip Tambak Oso" folklore as the medium, which is packed in the form of Wayang Sarip (puppet) show. The design used is an experimental wayang model of paper material into characters in the legend Sarip Tambak Oso. The theme of this program is the development of assessment and intervention for human happiness. The performances contains the contents of local wisdom, which is aimed to two generations, which are the early childhood and adolescent children. These early childhood children are students of kindergarten Dharmawanita Kesung Kulon Krian, and the teenagers are members of Karang Taruna Perumahan MCA, RW 5 Boro Tanggulangin village. The objectives are: (1) to develop the creation and making of puppet show legend for the proponents and participants, (2) to help create understanding and love of PKM participants to the meaning of folklore "Sarip Tambak Oso", (3) improving analytical skill, using legend and writing articles for the program proponent